La conférence sur le climat de Copenhague - Yakemtchouk, Romain (Rivista di studi politici internazionali, 2010)
The 193 Heads of State and Heads of Government present at the United Nations Climate Change Conference 2009 in Copenhagen have underlined that the climate change is one of the greatest challenges of our time, and have agreed that deep cuts in global emissions are required with a view to reduce emissions so as to hold the increase in global temperature below 2 degrees Celsius. Nationally mitigation actions subsequently taken by the Parties will ensure that national sovereignty is respected. The developed countries (United States, Japan and European Union) shall provide adequate and sustainable finance resources to support the implementation of adaptation action in least developing countries. Next Conference on the Protection of Climate will take place on December 2010 in Mexico. La conférence des Nations unies sur le changement climatique, qui a réuni au mois de décembre 2009 à Copenhague 193 pays, a reconnu que le problème du changement climatique est une des plus grandes préoccupations de notre temps. Elle a adopté une Déclaration fixant la limite du réchauffement climatique à 2 C° d'ici 2050. La vérification des limites des émissions devra respecter la souveraineté nationale des États concernés. Les États-Unis, le Japon et l'Union européenne se sont engagés à verser une substantielle aide financière aux pays vulnérables. La prochaine conférence climatique se tiendra en décembre 2010 à Mexico. MOTS-CLÉS: Émissions de CO2 ; Onu; Rélations extérieures de l'Ue; Protocole de Kyoto; Aide aux pays vulnérables.